The Development of Quranic Exegesis In Indonesia: A General Typology - H. Helmiati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The development of the interpretation of the Qur'an in Indonesia is strongly influenced by the development of intellectual dynamics in this region. The characteristics of the development of interpretations are very significantly influenced by the socio-historical changes and intellectual development of the Indonesian people. In this context there are four interpretive typologies which are also stages of the development of interpretations in Indonesia, namely: the first period of interpretation of the translation, in which the interpreters of the archipelago rely heavily on Middle Eastern interpreters as a reference and most works are explored from Middle Eastern commentators. Second, the modern period, where the interpretation that developed was the influence of modern developments in Islam. Third, the period of contextual interpretation, that is, interpretations are written on certain topics.